2016
DOI: 10.1021/acs.jafc.6b01293
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elucidation of Enzymatically Synthesized Galacto-oligosaccharides Using Ion-Mobility Spectrometry–Tandem Mass Spectrometry

Abstract: Galacto-oligosaccharides (GOS) represent a diverse group of well-characterized prebiotic ingredients derived from lactose in a reaction catalyzed with β-galactosidases. Enzymatic transgalactosylation results in a mixture of compounds of various degrees of polymerization and types of linkages. Because structure plays an important role in terms of prebiotic activity, it is of crucial importance to provide an insight into the mechanism of transgalactosylation reaction and occurrence of different types of β-linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Namely, the reaction mixture consisted of GOS (tri‐saccharides ‐GOS3 and tetra‐saccharides ‐ GOS4), lactose, glucose and galactose. Such composition was rather expected, bearing in mind that β‐galactosidase from A. oryzae exhibits a low tendency towards creating other disaccharides, as well as the higher oligosaccharides (Carević et al ., ). Additionally, it can be seen that obtained results (total GOS concentrations) using both substrates are quite similar (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Namely, the reaction mixture consisted of GOS (tri‐saccharides ‐GOS3 and tetra‐saccharides ‐ GOS4), lactose, glucose and galactose. Such composition was rather expected, bearing in mind that β‐galactosidase from A. oryzae exhibits a low tendency towards creating other disaccharides, as well as the higher oligosaccharides (Carević et al ., ). Additionally, it can be seen that obtained results (total GOS concentrations) using both substrates are quite similar (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Throughout this study, the possibility of economically viable whey utilization for GOS synthesis using enzyme β‐galactosidase from A. oryzae was examined. This enzyme was chosen on the basis of its availability, relatively low prices, and more importantly, our previous findings claiming its outstanding transgalactosylation activity (Carević et al ., ,b).…”
Section: Resultsmentioning
confidence: 99%
“…Products of transgalactosylation are depicted by trisaccharide (GOS3) peak (t R =8.733 min) and tetrasaccharide (GOS4) peak (t R =8.213 min). In our previous study (Carević et al, 2016a) was confirmed by IMS/MS-MS analysis that other disaccharides, except the lactose, are not pre-sent in the reaction mixture and that GOS3 and GOS4 peaks exclusively with β(1→6) and β(1→3) glycosidic linkages are the only transgalactosylation products. …”
Section: Resultsmentioning
confidence: 70%
“…GOS represent a diverse group of water soluble carbohydrates consisting of several galactose and usually one terminal glu-cose unit, that can notably vary in polymerization degree, type of linkages, and more importantly in their properties (Urrutia et al, 2013, Carević et al, 2016a. They are marked as non-digestible compounds, recognized as prebiotics owing to the fact that are selectively metabolized by some favorable intestinal microbiota, particularly bifidobacteria and lactobacilli, providing their proliferation and promotion of their activity (Arreola et al, 2014;Hong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The most studied β-galactosidases for GOS synthesis from lactose are those from strains of Kluyveromyces [15,16], Aspergillus [17,18], Bacillus [19,20], and Bifidobacterium [5,21]. GOS production with microbial β-galactosidases could be performed using crude, purified, recombinant, or immobilized enzymes and also whole cells [2,8].…”
Section: Introductionmentioning
confidence: 99%